2020
DOI: 10.1037/pspi0000234
|View full text |Cite
|
Sign up to set email alerts
|

Access is not enough: Cultural mismatch persists to limit first-generation students’ opportunities for achievement throughout college.

Abstract: United States higher education prioritizes independence as the cultural ideal. As a result, firstgeneration students (neither parent has a four-year degree) often confront an initial cultural mismatch early on in college settings: they endorse relatively interdependent cultural norms that diverge from the independent cultural ideal. This initial cultural mismatch can lead first-generation students to perform less well academically compared with continuing-generation students (one or more parents have a four-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
131
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 145 publications
3
131
0
1
Order By: Relevance
“…Those from different backgrounds or cultures-where, for example, norms, language, agency, and goals may be more interdependently orientated, emphasizing the role of family and communitycan feel that the language and norms used by those institutions are unfamiliar and alien. This can increase how difficult they perceive their academic tasks to be, discourage them from making use of the resources that are available to support them, increase feelings of being an imposter, and decrease their performance (Canning, Lacosse, Kroeper, & Murphy, 2019a, Dittmann, Stephens, & Townsend, 2020Okagaki, 2001;Phillips, Stephens, & Townsend, 2015;Stephens et al, 2012a;Stephens, Dittmann, & Townsend, 2014a;Stephens, Fryberg, & Markus, 2010;Stephens, Townsend, Markus, & Phillips, 2012c).…”
Section: Group Orientations: Norms Values and Sense Of Agencymentioning
confidence: 99%
“…Those from different backgrounds or cultures-where, for example, norms, language, agency, and goals may be more interdependently orientated, emphasizing the role of family and communitycan feel that the language and norms used by those institutions are unfamiliar and alien. This can increase how difficult they perceive their academic tasks to be, discourage them from making use of the resources that are available to support them, increase feelings of being an imposter, and decrease their performance (Canning, Lacosse, Kroeper, & Murphy, 2019a, Dittmann, Stephens, & Townsend, 2020Okagaki, 2001;Phillips, Stephens, & Townsend, 2015;Stephens et al, 2012a;Stephens, Dittmann, & Townsend, 2014a;Stephens, Fryberg, & Markus, 2010;Stephens, Townsend, Markus, & Phillips, 2012c).…”
Section: Group Orientations: Norms Values and Sense Of Agencymentioning
confidence: 99%
“…Furthermore, this work has shown that cultural assumptions developed from prior social class experiences can lead people to experience their current contexts differently. For example, studies have shown that colleges and professional workplaces can be more stressful and challenging for people who come from working‐class backgrounds because these contexts tend to be built around upper‐ and middle‐class cultural assumptions (Belmi & Laurin, 2016; Belmi, Neale, Reiff, & Ulfe, 2020; Dittmann, Stephens, & Townsend, 2020; Phillips, Stephens, Townsend, & Goudeau, 2020; Rivera, 2016; Stephens, Townsend, Markus, & Phillips, 2012).…”
Section: Current Perspectives On Social Classmentioning
confidence: 99%
“…However, largely missing from the previous research is the consideration that people are shaped not only by their place in, but also by their movement throughout, the hierarchy. For instance, emerging work considering social class transitions finds that individuals can learn new norms in new class environments (e.g., Herrmann & Varnum, 2018a, 2018b), and that class background effects can be exacerbated by organizational context (Phillips et al, 2020). Further, this dynamic perspective emphasizes not only the negatives of change (e.g., cultural mismatch), but also the positives (e.g., resilience, cultural flexibility, empathy; Martin & Côté, 2019).…”
Section: New Perspectives On the Psychology Of Social Class Changementioning
confidence: 99%
See 2 more Smart Citations